Identifying the features in histograms of increments in hazardous parameters of the gas environment at the ignition of materials in unhermetic premises - Tolok, Igor; Pospelov, Boris; Rybka, Evgeniy; Kozar, Yurii; Krainiukov, Olekcii; Volovyk, Volodymyr; Bogatov, Oleg; Manzhura, Svyatoslav; Ushkats, Svitlana; Tishechkina, Kateryna (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the histograms of increments in hazardous parameters of the gas environment in a leaky room in the absence and presence of fires of materials. The task of early detection of fires of materials in rooms was addressed. A methodology for determining the histograms of increments of arbitrary hazardous parameters based on samples of arbitrary size from controlled parameters was substantiated. A laboratory experiment was performed to identify the features of the histograms of increments of carbon monoxide concentration, specific optical density of smoke and temperature of the gas environment at intervals of reliable absence and occurrence of fires of alcohol, paper, wood, and textiles. The results indicate that hazardous parameters change over time non-stationarily and are of a complex nature. It was found that for the concentration of carbon monoxide, the specific optical density of smoke and the temperature of the gas medium in the interval of alcohol ignition, the number of modes of the histograms of increments is 9, 8, and 4, and the spread is 0–(+0.3), –0.07–(+0.09), and 0–(+0.32), respectively. When paper ignites, the histograms of increments of hazardous parameters have 10, 3, and 4 modes and the spread of increments is –0.06–(+0.21), ±(0.02), and –0.16–(+0.32), respectively. When wood ignites, the shape of the histogram of increments for the concentration of carbon monoxide is characterized by 4 modes and the spread is 0–(+0.09). The shape of the histograms of increments of the specific optical density of smoke and the temperature of the gas medium during the ignition of wood does not change significantly. The shape of the histogram of the increments of the carbon monoxide concentration during textile ignition is characterized by 3 modes and a spread of ±0.03, and the temperature – by two modes and a spread of 0–(+0.16). These features of the histograms could be used in practice as a sign of early detection of fires for their prompt extinguishing and prevention of fire evolution